Solve the given expression to obtain the value of x:
$\dfrac{{2x + 7}}{3} = \left( {x + 4} \right)$
Answer
Verified
509.4k+ views
Hint – In this question we need to solve for the value of x, use cross multiplication along with a simple simplification technique to solve the given equation for the value of x.
Complete step-by-step answer:
Given equation is
$\dfrac{{2x + 7}}{3} = \left( {x + 4} \right)$
Now the given equation is also written as
$\dfrac{{2x + 7}}{3} = \dfrac{{x + 4}}{1}$
Now apply cross multiplication method (i.e. (2x + 1) is multiplied by 1 and (x + 4) is multiplied by 3)
$ \Rightarrow 1\left( {2x + 7} \right) = 3\left( {x + 4} \right)$
Now simplify the above equation we have,
$ \Rightarrow 2x + 7 = 3x + 12$
Now shifting the variables i.e. 3x to L.H.S and 7 to R.H.S we have
$ \Rightarrow 2x - 3x = 12 - 7$
$ \Rightarrow - x = 5$
Now multiply by -1 we have,
$ \Rightarrow x = - 5$
So, this is the required solution of the given equation.
So, this is the required answer.
Note – Whenever we face such types of problems the key concept is simply to use basic techniques of cross multiplication and subtraction of terms with the same variables. This concept will help you get on the right track to reach the answer.
Complete step-by-step answer:
Given equation is
$\dfrac{{2x + 7}}{3} = \left( {x + 4} \right)$
Now the given equation is also written as
$\dfrac{{2x + 7}}{3} = \dfrac{{x + 4}}{1}$
Now apply cross multiplication method (i.e. (2x + 1) is multiplied by 1 and (x + 4) is multiplied by 3)
$ \Rightarrow 1\left( {2x + 7} \right) = 3\left( {x + 4} \right)$
Now simplify the above equation we have,
$ \Rightarrow 2x + 7 = 3x + 12$
Now shifting the variables i.e. 3x to L.H.S and 7 to R.H.S we have
$ \Rightarrow 2x - 3x = 12 - 7$
$ \Rightarrow - x = 5$
Now multiply by -1 we have,
$ \Rightarrow x = - 5$
So, this is the required solution of the given equation.
So, this is the required answer.
Note – Whenever we face such types of problems the key concept is simply to use basic techniques of cross multiplication and subtraction of terms with the same variables. This concept will help you get on the right track to reach the answer.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
When people say No pun intended what does that mea class 8 english CBSE
In Indian rupees 1 trillion is equal to how many c class 8 maths CBSE
How many ounces are in 500 mL class 8 maths CBSE
Which king started the organization of the Kumbh fair class 8 social science CBSE
What is BLO What is the full form of BLO class 8 social science CBSE
Advantages and disadvantages of science